(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This study examines the institutional development of the insurance sector in the context of the digital economy. It analyzes the impact of digital technologies, including artificial intelligence, Big Data, and digital platforms, on institutional structures, governance mechanisms, and operational efficiency. The findings indicate that digital transformation enhances flexibility, transparency, and innovation within insurance institutions, while also introducing new challenges such as cybersecurity risks and regulatory adaptation. The study highlights the importance of aligning technological advancement with institutional reforms for sustainable development.